Another Case of Glucose Transporter 1 Deficiency Syndrome with Periventricular Calcification, Cataracts, Hemolysis, and Pseudohyperkalemia - Shibata, Takashi; Kobayashi, Katsuhiro; Yoshinaga, Harumi; Ono, Hiroaki; Shinpo, Michiko; Kagitani-Shimono, Kuriko (Neuropediatrics, 2017)
Glucose transporter 1 (GLUT1) deficiency syndrome (GLUT1DS) is a disorder resulting from shortage of energy in the brain caused by reduced GLUT1 activity. Its common clinical symptoms include seizures, microcephaly, intellectual disability, abnormal ocular movements, ataxia, and dystonia. We report a case of GLUT1DS with unusual symptoms, including periventricular calcification. The patient is a Japanese girl, whose seizures had always evolved into status epilepticus since she was 4 months old. She also had cataracts and horizontal nystagmus. Neuroimaging studies showed periventricular calcification and brain atrophy. Laboratory data revealed pseudohyperkalemia, reticulocyte increase, and hypoglycorrhachia. A mutation of c1306_1308delATC (p.Ile436del) was identified in the SLC2A1 gene, and she was thus diagnosed with GLUT1DS. A case with the identical SLC2A1 gene mutation and similar clinical findings was previously reported by Bawazir et al (2012). The leak of monovalent cations through the red cell membrane causes hemolysis in such patients, and a similar phenomenon may occur at the blood–brain barrier and the lens epithelium. After commencing ketogenic diet therapy, the electroencephalogram (EEG) abnormalities improved markedly and the patient's development advanced. Clinicians should be aware of atypical GLUT1DS.
Keywords: GLUT1 deficiency; SLC2A1 gene; cation leak; stomatin; ketogenic diet therapy